Smart System To Prevent Fire Breakouts Of Lpg Cylinder - Manoharan.S, Abinaya.R, Bharathi.P, Arunkumar.S, Priyadharshini.V (International Journal of Modern Agriculture, 2021)
The project titled â€œSmart System to Prevent Fire Breakouts Of LPG Cylinderâ€ is designed with the aim of preventing major fire breakouts which may lead to loss of life and property. Nowadays LPG has become the basic necessity for our life. The proposed system is mainly focused on detecting the LPG leakage and the alarming system gets turned on once the gas leakage detected by the sensor is beyond the threshold level(70 ppm) and this system provides an additional feature by expelling the leaked gas through the window. T he GSM module which is present in this system is used to send information via SMS to the registered mobile number as soon as the alarming system gets turned on to provide an information. The alarming system gets turned off when the sensor encounters the gas level present in the room is less than the threshold level(70 ppm).